A Foot in the (Revolving) Door? A Preliminary Evaluation of Tasmania's Mental Health Diversion List - Graham, Hannah (2007)
There is a strong intersection between the health system and the criminal justice system, as exemplified by problems encountered with offenders with a mental illness. Therapeutic jurisprudence and the problem solving court model seek to overcome issues associated with the failure of traditional sentencing for this offender population, the ‘revolving door’ and deficits in treatment support. Evaluation research was utilised in this study to conduct a preliminary assessment of the effectiveness of the Mental Health Diversion List pilot project. Data sources comprised in this study include: courtroom observation of the Diversion List sittings, interviews with practitioners, a defendant interview, project team meeting observation, and court documentation. Rich qualitative data contributed to the emergence of various themes and issues indicating the general success of the List. However, different practitioner perspectives and debates revealed opportunities for further development. Overall, the preliminary evaluation concluded that the therapeutic problem solving approach adopted in the Mental Health Diversion List pilot project is working well. Recommendations are made for further development and enhancement that can take place